Occurrence of gastrointestinal parasites infection in large felines (Puma concolor, Panthera leo, Panthera pardus, Panthera onca) in Zoo Negara, Ulu Kelang - Ghazali, Maria Syafiqah (2018)
The present study was conducted to observe the occurrence of gastrointestinal parasites in large felines in the National Zoo of Malaysia located in Ulu Kelang, Gombak District, Selangor, which was undertaken for two weeks in January 2018. Ten fecal samples were collected from pumas (Puma concolor, n = 5), African lions (Panthera leo, n = 4), spotted leopard (Panthera pardus, n = 1) and black panther (Panthera onca, n = 1). All fecal samples were collected in the morning according to individual animals and kept in an ice box for transportation to Parasitology Laboratory in Faculty of Veterinary Medicine, Universiti Putra Malaysia, Serdang. All samples were examined for parasite eggs, larvae and oocysts by simple floatation technique by using salt solution and formalin – ether sedimentation technique. All large feline members in Zoo Negara were infected with gastrointestinal parasite. A total of six species of gastrointestinal parasites recovered including four nematodes (Toxocara cati, Ancylostoma spp., Toxascaris leonina, and Oxyuris spp.), a cestode (Spirometra spp.) and a protozoa (unknown). This study suggests that among different helminth infections, the occurrence of nematode infections was higher (100 %; n=10/10) than cestode infection (10 %; n=1/10)and protozoa infection (10 %; n=1/10). Majority (n=5/10) of the large felines had mixed infections of Toxocara spp.and Ancylostoma spp.